Epidemiologic Study of the Discoid Meniscus: Investigating Demographic-Based Predictors in Large-Scale Claims Database. Issue 7 (30th July 2021) - Randhawa, Sahej S; Tran, Emily P; Segovia, Nicole A; Ganley, Theodore J; Tompkins, Marc; Ellis, Henry; Shea, Kevin G
Background: Discoid meniscus epidemiology remains poorly defined for race and sex, in part, due to limitations of retrospective studies and small case series. A better understanding of epidemiology may improve clinical care and diagnostic precision. Purpose: Our purpose is to better define the epidemiology of discoid meniscus by analyzing a large, national database for incidence rates by sex and race. Methods: Analysis was conducted on the national-scale Clinformatics Data Mart Database by Optum. Proportions of the database's racial categories (Asian, Black, Hispanic, White, and Unknown) in the total population of diagnosed discoid meniscus cases (n = 1, 006) were calculated and compared via chi-squared tests to the total database population (n = 65, 759, 970). This analysis was repeated for the population of patients who received knee arthroscopies (81, 205). Incidence rates were calculated from these populations as well. Finally, a multivariable logistic regression analysis based on the population of arthroscopy-receiving patients was performed to control for age, reported gender, and income. Results: Proportions of Asian, Black, Hispanic, and White racial categories in the discoid meniscus group were 5.7%, 7.3%, 20.6%, 66.4%, respectively; the proportions of each racial category in the total population were 5.2%, 10.3%, 13.5%, 71.0%, respectively. Incidence rates (per 10, 000) for these groups in the arthroscopy population were 72.9, 25.6, 49.2, 25.6, respectively. Our logistic regression model indicated that race was not a statistically significant predictor for our dataset after income adjusting. Adjusting for other covariates, the odds of a discoid meniscus diagnosis decreased by 6% for each increase in age (p < 0.001) and were 41% lower for males compared to females (p < 0.001).Conclusion : Prior studies have suggested that race (Asian and Hispanic, is a predictor of higher incidence of discoid meniscus – this study did not show a difference in incidence based upon race. Patient sex and age was identified as significant predictors for discoid meniscus, and increasing age showed a decreasing incidence of this condition. This study's analysis of a large, national claims database allows for a comprehensive epidemiological study on this topic, offering proportions and incidence rates by race appropriate for application to the US population. Its conclusions promote patient sex and age as significant predictors and question the beliefs on race-associated incidence often based on comparing results from the corpus of single-site cohort studies. Tables/Figures: